2016
DOI: 10.1007/s00381-016-3243-7
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous involution of pediatric low-grade gliomas: high expression of cannabinoid receptor 1 (CNR1) at the time of diagnosis may indicate involvement of the endocannabinoid system

Abstract: The P-LGG, which remained stable or that presented spontaneous involution after STR, showed significantly higher CNR1 expression at the time of diagnosis. We hypothesize that high expression levels of CNR1 provide tumor susceptibility to the antitumor effects of circulating endocannabinoids like anandamide, resulting in tumor involution. This corroborates with reports suggesting that CNR1 agonists and activators of the endocannabinoid system may represent therapeutic opportunities for children with LGG. We als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 21 publications
0
17
0
1
Order By: Relevance
“…However, recent studies have demonstrated opposite results, showing CB 1 receptors to be highly expressed in high‐grade gliomas compared to low‐grade tumours and healthy brain samples (Wu et al, ). Interestingly, these results have also been found in samples of low‐grade paediatric glioma, where overexpression has been associated with tumour regression, due to the apoptosis and cell cycle arrest induced by activation of CB 1 receptors by endocannabinoids (Sredni et al, ). Concerning CB 2 receptors, Schley et al .…”
Section: Endocannabinoid System Expression In Cancermentioning
confidence: 74%
“…However, recent studies have demonstrated opposite results, showing CB 1 receptors to be highly expressed in high‐grade gliomas compared to low‐grade tumours and healthy brain samples (Wu et al, ). Interestingly, these results have also been found in samples of low‐grade paediatric glioma, where overexpression has been associated with tumour regression, due to the apoptosis and cell cycle arrest induced by activation of CB 1 receptors by endocannabinoids (Sredni et al, ). Concerning CB 2 receptors, Schley et al .…”
Section: Endocannabinoid System Expression In Cancermentioning
confidence: 74%
“…Previous studies have reported that synapse loss in noise and age-induced hearing loss ( Sergeyenko et al, 2013 ; Espejo-Porras et al, 2015 ; Liberman and Kujawa, 2017 ) which was not associated with loss of OHCs or ABR threshold shifts. This type of cochlea synaptopathy is known as “hidden hearing loss” ( Liberman and Kujawa, 2017 ) and is detected by a reduction in wave I supra-threshold amplitude ( Sredni et al, 2016 ; Liberman and Kujawa, 2017 ). The present study revealed an important “tonic” role of the endocannabinoid/CB2R system to preserve synaptic integrity under normal condition which was unmasked by the application of CB2R antagonist.…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies showed that cannabinoids can induce apoptosis of glioma cells via CB1R and CB2R dependent de novo synthesis of the sphingolipid ceramide showing pro-apoptotic properties [47,94,[134][135][136][137]. CB1R is over-expressed in glioblastomas [138] and paediatric low-grade gliomas, and is implicated in tumour involution induced by apoptosis and cell-cycle arrest upon activation [139]. CB 2 R is also highly expressed in glioblastomas and astrocytomas and related to tumour grade [94,137,138,140,141].…”
Section: Central Nervous System Malignanciesmentioning
confidence: 99%